Information disclosure and the market for acquiring technology companies - Chondrakis, George; Serrano, Carlos J.; Ziedonis, Rosemarie H. (Strategic Management Journal, 2021)
Research Summary The market for acquiring technology companies is rife with information frictions. Although such frictions can stifle trading activity, they also provide room for strategic gain. We investigate this dual role of information frictions by exploiting an institutional reform that releases technological information to the public domain. Leveraging cross‐sectoral variation in the magnitude of disclosure, we find an increase in acquisition activity and in the technological distance between matched pairings. In line with predictions from strategic factor market theory, however, we also find a disproportionate decline in acquirer returns on average. Our findings suggest that information disclosed through the reform‐facilitated exchange in the takeover market yet had a leveling effect on the returns to acquirers. Managerial Summary Firms acquire technology‐oriented companies to complement internal R&D projects and accelerate the innovation process. But identifying promising targets is challenging, not least due to the lack of information about the value of acquired technologies. This study investigates an information shock and tests its effects on the market for acquiring technology‐intensive companies. We find that greater disclosure of technological information to the public domain intensifies trading activity and allows acquirers to better identify and assess targets outside their core technological domains. But it also reduces the returns to acquirers. In combination, our findings illuminate a dual role of information disclosure: placing more information into the public domain may facilitate trade in corporate takeover markets while simultaneously restricting acquirer opportunities for strategic gain.